Influencia de diferentes técnicas de inserción del agente autoadhesivo en la formación de burbujas en proceso de cementación del endoposte - Valladares Paredes, Harold Steve (2017)
Objectives: To identify the influence of different techniques of insertion of the self - adhesive agent in the formation of bubbles in cementation process of the endoposte. Method: 30 unirradicular premolars extracted with orthodontic purposes were submitted to endodontics. Randomly the sample was divided into three groups according to the method of cement insertion in the lentulo group, lime group, intrarradicular tip group. Subsequently, the cementing procedure of fiber bolts was performed using a self-conditioning and self-adhesive resin type cement. The samples separated by groups were cut at the apical third level and received a special preparation prior to observation in scanning electron microscope TESCAN MIRA. The samples were observed with a voltage of 5 Kv and several microphotographs of their topography were obtained. Results: Considering the percentage of area observed with presence of bubbles, the averages obtained are; 3.03 percent for lent, 1.54 percent for lime and 2.73 percent for tip. Which determines that the lime group showed a lower formation of air bubbles in the resinous cement followed by the tip group and ending with the lentulate group. However, these differences are not statistically significant, therefore, the null hypothesis is accepted. "Insertion techniques do not influence the presence of bubbles in the post cementation process". Conclusion: In the three techniques applied in this study it was evidenced the presence of trapped air which indicates that none of them in infallible. As in all three techniques, optimum results were obtained in some cases. In the technique of application of the cement with intrarradicular tip that according to the hypothesis should be shown as the most efficient, showed in some cases larger air bubbles with respect to the other two techniques.